Drivers of Malaysian Youth Entrepreneurship / Nor Akma Shahira Azman, Nurul Hidayana Mohd Noor and Mahazril 'Aini Yaacob - Azman, Nor Akma Shahira; Mohd Noor, Nurul Hidayana; Yaacob, Mahazril 'Aini (2021)
Youth entrepreneurship refers to the practical application by youths of enterprising qualities such as initiative, innovation, creativity, and risk-taking into their work using appropriate skills necessary for success in the environment and culture. The National Youth Policy 2015 which replaced it redefined youth as those aged between 15 and 30 years (UNICEF Malaysia, 2020). Entrepreneurship can be determined as the backbone of national economics' progress (Voda & Florea, 2019). It develops the potential of the human through the formation of self-employment and job creation (Kamrul Hassan, 2020). Entrepreneurship also gives benefits to the people in terms of innovation creation, diversity, economic growth which leads to competitiveness (Diandra & Azmy, 2020). The theory of planned behaviour by Ajzen is practicable in this study. It is because the entrepreneurial activity is a planned, intentional behavior, and the formation of entrepreneurial intentions depends on personal attitudes. This theory highlights the relations between beliefs and behavior, stating that the attitude towards behavior, subjective norms, and perceived behavioral control together make up for an individual's behaviors and intentions. Entrepreneurship skills must be developed among the youth especially universities students so that they will have other options in pursuing their career after graduating. The youth's entrepreneurship intention is influenced by entrepreneurial self-efficacy (Kamrul Hassan, 2020), entrepreneurial education (Voda & Florea, 2019; Hassan, Lashari, & Basit, 2021; Yusoff, Zainol, & Ibrahim, 2015), university perceived support (Yusoff, Zainol, & Ibrahim, 2015; Bagheri & Lope Pihie; Nasiru, Keat, & Bhatti, 2015) and entrepreneurial network (Kamrul Hassan, 2020; Wang, Shang, & Zhang, 2019).